Prevalence of Chlamydia trachomatis among Childbearing Age Women in India: A Systematic Review - Kalpana Betha; Jamie M. Robertson; Gong Tang; Catherine L. Haggerty (Hindawi Limited, 2016)
Background. Infection with Chlamydia trachomatis (CT) can lead to reproductive sequelae. Information on the general population of childbearing age women in India is sparse. We reviewed the literature on CT prevalence within the general population of reproductive aged women in order to improve the efforts of public health screening programs and interventions. Objective. To conduct a literature review to determine the prevalence of Chlamydia trachomatis among childbearing age women in India. Search Strategy. Ovid Medline and PubMed databases were searched for articles from January 1, 2003, through December 31, 2014. Search terms included "Chlamydia trachomatis", "CT", "prevalence", "India", and "sexually transmitted infections". Selection Criteria. Studies on prevalence data for CT among women of childbearing age (15-45) living in India were included. Data Collection and Analysis. Articles that met the inclusion criteria were extracted by two readers and discrepancies solved through discussion. Results. Reported prevalence of active CT infection among lower risk groups ranged from 0.1% to 1.1% and in higher risk group from 2.7% to 28.5%. Conclusion. CT prevalence among women in India is comparable to other countries. Screening programs to prevent adverse outcomes among Indian women of childbearing age and their offspring are warranted.